(untitled) (Kronika Bydgoska, 2010)
Archaeological excavations were located on the site of Gdańska Gateway relics, and the eastem part of the church with the sanctuary of the Church of Our Lady. Archaeologists examined also the churchyard and the brick fence surrounding the monastery to the north and the east. Documented were also the relics of a brick building with a basement, adjoining a municipal gateway directly to the west, functioning as a chapel. An unknown stone foundation was also found as a relic of a medieval belfry connected with a wooden church. The parts of the Carmelite brick church examined with the use of excavations were the crowns of stone-brick foundations of the sanctuary and the eastem part of the church nave, and the crowns of walls of the church chapels added to the north, along with burial crypts. The uncovered relics of the sanctuary and partially the northem main wali of the church datę back to the late 16th century, whereas the relics of chapels were added to the northern wali of the church in the 17th-18th centuries. The church and the monasterial brick fence were constructed at the same time as the brick Gdańska Gateway, in 1584. The excavations in the churchyard facilitated the new identification in the scope Of topography and the successive stages of settlement in Przedmieście Gdańskie District and starting anthropological examinations in the scope of the biological State of Bydgoszcz residents in the 15th-18th centuries.